Health-resort fee and a stay in a health-resort hospital – comments based on the general interpretation of the Minister of Finance - Jacek Wantoch-Rekowski (Prawo Budżetowe Państwa i Samorządu)
The publication presents the argumentation of the Minister of Finance included in the general interpretation of 3 October 2014 concerning the interpretation of Article 17 paragraph 2 clause 2 of the Act on Local Taxes and Fees. It was explained what was understood by the term “hospital” before 3 October 2014 and what changed in this subject after the general interpretation of the Minister of Finance was issued. It was emphasized that now the health-resort fee should not be charged from legal persons staying in health resort hospitals.